Developing Dayah as Religious Tourism Destination in Aceh - Heriani, Heriani; Baiquni, M; Wijono, Djoko; Widyaningsih, Yulia Arisnani (E-Journal of Tourism; Volume 5 Number 1 (March 2018)DO - 10.24922/eot.v5i1.38459, 2018)
Aceh has several religious tourism destinations, especially the historic mosques and the graves of the Ulama but it turns out that many tourists also come and visit Dayah. The flow of tourist arrivals to Dayah has not been well organized, whereas the potential of Dayah as a religious tourism destination is very large to be developed. This study aims to provide an overview of the potential and strategy of Dayah development as one of the religious tourism destinations in Aceh. The research method used in this research is qualitative with observation and interview based on primary and secondary data. The results show that some Dayah in Aceh who have great potential need to be developed as a religious tourism destination. The potential development efforts can be through several strategies that involve the role of government, Ulama and Dayah managers and the Dayah community. Keywords: Dayah, potential, strategy, religious, tourism